To Serve and Collect : Chicago Politics and Police Corruption from the Lager Beer Riot to the Summerdale Scandal, 1855-1960. - Lindberg, Richard C. (Southern Illinois University Press, 1998)
Crooked politicians, gangsters, madams, and cops on the take: To Serve and Collect tells the story of Chicago during its formative years through the history of its legendary police department.